2005
DOI: 10.1096/fj.04-3213fje
|View full text |Cite
|
Sign up to set email alerts
|

p53 is a suppressor of inflammatory response in mice

Abstract: Chronic inflammation is known to promote cancer, suggesting that negative regulation of inflammation is likely to be tumor suppressive. We found that p53 is a general inhibitor of inflammation that acts as an antagonist of nuclear factor kappaB (NFkappaB). We first observed striking similarities in global gene expression profiles in human prostate cancer cells LNCaP transduced with p53 inhibitory genetic element or treated with TNF, suggesting that p53 inhibits transcription of TNF-inducible genes that are lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
162
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(178 citation statements)
references
References 61 publications
(81 reference statements)
14
162
2
Order By: Relevance
“…Second, normally proliferation of cells with DNA damage would have been blocked through G2/M checkpoint activation and those cells would either persist indefinitely in the absence of the 'promotion' signal or would be eliminated through p53-mediated pro-apoptotic pathway. However, this pathway is antagonized by activation of the NF-kB-mediated proinflammatory pathway (Komarova et al, 2005;Karin et al, 2006), which allows cells with unrepaired DNA damage to avoid apoptosis and enter the cell cycle. In TB lesions, activation of the NF-kB pathway in macrophages as well as in epithelial cells may be triggered by at least three activation pathways, namely oxidative damage, toll-like receptor ligands of bacterial origin and TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…Second, normally proliferation of cells with DNA damage would have been blocked through G2/M checkpoint activation and those cells would either persist indefinitely in the absence of the 'promotion' signal or would be eliminated through p53-mediated pro-apoptotic pathway. However, this pathway is antagonized by activation of the NF-kB-mediated proinflammatory pathway (Komarova et al, 2005;Karin et al, 2006), which allows cells with unrepaired DNA damage to avoid apoptosis and enter the cell cycle. In TB lesions, activation of the NF-kB pathway in macrophages as well as in epithelial cells may be triggered by at least three activation pathways, namely oxidative damage, toll-like receptor ligands of bacterial origin and TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…In inflammatory conditions, p53 À/À mice have an increased recruitment of macrophages and a prolonged activation of neutrophils. 64 As a converse to this, it has been shown that pro-inflammatory macrophage migration inhibitory factor (MIF) interferes with p53 function, thus providing a link between inflammation, atherosclerosis and cancer. 65 MIF is overexpressed in tumors and correlates with tumor aggression and downregulation of p53 apoptosis.…”
Section: Tp53 and Inflammationmentioning
confidence: 99%
“…Another recent work by Komarova et.al. 37 showed p53 as a suppressor of inflammatory response in mice and proposed a general 'buffering' role of these reciprocally controlled pathways. This 'pharmacological tuning', as proposed by them, would offer the potential of targeting both the pathways in one attempt.…”
Section: R-roscovitine Inhibitsmentioning
confidence: 99%